2014
DOI: 10.1177/0004563214531739
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine catabolism is driven mainly towards nitric oxide synthesis in the erythrocytes of patients with type 2 diabetes at first clinical onset

Abstract: l-Arg catabolism is driven mainly towards NO synthesis in RBCs of patients with type 2 diabetes at first clinical onset. The decreased RBC arginase activity could be considered a potential mechanism of increased RBC NO production in early diabetes. Therefore, the RBC pool would represent a potentially compensatory intravascular compartment for endothelial dysfunction in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Arginase I is known to play an important role in the regulation of the immune system and pathological development as it negatively regulates NO synthesis [ 78 , 79 ]. Different cardiovascular disease states are described which exhibit decreased NO availability and increased arginase activity such as hypertension and diabetes [ 47 , 79 81 ]. Increased arginase I activity was found in young RBC from type 2 diabetics and activity decreased with increasing cell age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arginase I is known to play an important role in the regulation of the immune system and pathological development as it negatively regulates NO synthesis [ 78 , 79 ]. Different cardiovascular disease states are described which exhibit decreased NO availability and increased arginase activity such as hypertension and diabetes [ 47 , 79 81 ]. Increased arginase I activity was found in young RBC from type 2 diabetics and activity decreased with increasing cell age.…”
Section: Discussionmentioning
confidence: 99%
“…Arginase, a key enzyme of the urea cycle, is a main regulator and competitor for RBC-NOS activity [ 44 , 45 ] Arginase I is expressed in a variety of cells [ 46 ] including RBC [ 47 ] and increased arginase expression and activity have been described in animal models [ 48 , 49 ] of diabetes mellitus and in diabetic tissue in humans, as well [ 50 ]. Both, arginase I and RBC-NOS compete for their common substrate L-arginine.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them show an increased RBC-NOS activation in RBCs from sickle cell anemia patients and a significant increase in cGMP levels within RBCs has also been found as compared to healthy subjects [25,26]. Recently, it was shown that NO production was higher in RBCs from patients with type 2 diabetes than in controls [27]. The decreased RBC arginase activity could be considered a potential mechanism for increased RBC NO production in early diabetes.…”
Section: Introductionmentioning
confidence: 97%
“…The decreased RBC arginase activity could be considered a potential mechanism for increased RBC NO production in early diabetes. Thus, the RBC pool may be a potentially compensatory intravascular compartment for endothelial dysfunction in diabetes [27]. More recently Bizjak et al [28], by a study on age-dependent changes of rheology and enzymatic properties in RBCs, showed highest RBC-NOS activation and NO production in old RBC, suggesting that this is probably required to counteract the negative impact of cell shrinkage on RBC deformability.…”
Section: Introductionmentioning
confidence: 98%
“…It has also been important for immunological surveillance [ 4 , 5 ]. It gets upregulated in vascular abnormalities [ 6 , 7 ], diabetes [ 8 ], hepatocellular carcinoma [ 9 ], cardiovascular diseases [ 10 ], and neuroinflammation [ 11 ]. Other roles of arginase have also been reviewed [ 12 ], showing impact of arginase on biological significance of arginine metabolism associated pathological conditions.…”
Section: Introductionmentioning
confidence: 99%